2000
DOI: 10.1128/iai.68.5.2553-2559.2000
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen YPMa Exacerbates the Virulence ofYersinia pseudotuberculosisin Mice

Abstract: The gram-negative bacterium Yersinia pseudotuberculosis is widely spread in nature and is responsible for sporadic infection in many animal species (10). Humans are commonly infected after ingestion of food or water contaminated with excreta of infected animals. Y. pseudotuberculosis causes acute ileitis and mesenteric lymphadenitis, sometimes complicated by septicemia (10, 26), but is also responsible for the occurrence of postinfection complications such as reactive arthritis and erythema nodosum (10,35,45,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Y. pseudotuberculosis, S. typhimurium and E. coli strains were grown at 28 uC, 37 uC and 37 uC, respectively, in Luria-Bertani (LB) broth or on agar plates. Mating experiments between E. coli and Y. pseudotuberculosis were plated on M9 minimum medium agar, as described previously (Carnoy et al, 2000). Ampicillin (100 mg ml ) and sucrose (10 %) were added to media for bacterial selection when necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. pseudotuberculosis, S. typhimurium and E. coli strains were grown at 28 uC, 37 uC and 37 uC, respectively, in Luria-Bertani (LB) broth or on agar plates. Mating experiments between E. coli and Y. pseudotuberculosis were plated on M9 minimum medium agar, as described previously (Carnoy et al, 2000). Ampicillin (100 mg ml ) and sucrose (10 %) were added to media for bacterial selection when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were kept in positive-pressure cabinets during experimentation, and mortality was monitored daily for 21 days after challenge. For each experimental infection, the presence of the virulence plasmid pYV was confirmed by PCR on bacterial thermolysates using primers YOPH1 and YOPH2, which are internal to yopH, a gene located on pYV (Carnoy et al, 2000). Infected animals were monitored for 3 weeks, and the 50 % lethal dose (LD 50 ) was calculated from groups of 5 (i.v.…”
mentioning
confidence: 99%
“…Y. pseudotuberculosis is also known to produce a superantigenic toxin, known as YPM (1,46) and then YPMa after the discovery of a variant (36). It was experimentally confirmed that YPMa is a virulence factor which exacerbates the toxicity of Y. pseudotuberculosis in systemic but not in gastroenteric infection in mice (11). Superantigen-producing strains could be separated into three clusters which contained YPMa, YPMb, or YPMc encoded by the ypmA, ypmB (36), and ypmC (10) genes, respectively.…”
mentioning
confidence: 99%
“…This molecule (designated YPM for Y. pseudotuberculosis-derived mitogen) is a 14.5-kDa protein able to induce proliferation of human T lymphocytes bearing V␤3, V␤9, V␤13.1, and V␤13.2 T-cell receptor variable regions (1,61). In vivo, YPM induces lethal shock in mice (44) and exacerbates the virulence of Y. pseudotuberculosis in a murine experimental model of systemic infection (13). To date, three YPM variants (YPMa, YPMb, and YPMc) have been described.…”
mentioning
confidence: 99%